Techniques utilised at 2017 Judo World Championship and their classification: comparisons between sexes, weight categories, winners and non-winners - Pereira Martins, F.; Scarano Dualiby Pinto de Souza, L.; Pinheiro de Campos, R.; Bromley, S. J.; Takito, M. Y.; Franchini, E. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2019)
Background. Judo throwing techniques are traditionally classified as ashi-waza (leg techniques), te-waza (arm techniques), koshiwaza (hip techniques) and sutemi-waza (sacrifice techniques). However, this classification has recently been criticised, and instead a 9-group classification system based on action characteristics (movement type, base of support, throw direction, and position of attack) has been proposed. Problem and aim. To determine the throwing techniques that resulted in score using this classification and compare weight categories, sexes and medal/non-medal winners during the 2017 Senior Judo World Championship. Method. The analysis included 756 throwing techniques that resulted in a score (over 601 matches) across the competition. Results. There was an association between technique classification and sex (c2 = 15.64; p = 0.048; Cramer's V = 0.144): females scored more frequently using the techniques from group 3 compared with males (c2 = 6.93; p = 0.009), whereas males scored more often using the techniques from group 8 compared with females (c2 = 5.55; p = 0.019). A significant relationship between technique classification and weight category (c2 = 106.19; p < 0.001; Cramer's V = 0.153) was observed, but there was no association between technique classification and World Championship classification (c2 = 9.55; p = 0.298; Cramer's V = 0.112). Additionally, a limited number of throwing techniques resulted in more than half of all scoring situations during this competition. Conclusions. Techniques types utilised by athletes differed according to sex and weight category, and that a few number of techniques were utilised in this top-level judo competition.